2021
DOI: 10.1142/s2737416521500137
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Citrus Flavonoid Tangeretin: A Promising Pharmacological Tool for the Treatment and Prevention of Zika fever and COVID-19

Abstract: It is of great importance for the pharmaceutical industry to find therapeutic substances extracted from natural sources, which are abundant, obtained with low costs and presenting the antiviral potential for the treatment of Zika virus (ZIKV) and COVID-19. Tangeretin (TAN) is a citrus polymethoxyflavone from Citrus reticulata peel oil with known antiviral activities, whose physico-chemical properties are not reported. The present study aimed to investigate by a theoretical screening of electronic, structural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Previous computational studies have revealed that taxifolin could be a potential inhibitor against the SARS-CoV-2 Mpro enzyme [33]. Moreover, tangeretin showed potential for the treatment and prevention of COVID-19 [34], while, hispidulin showed a better binding affinity to Mpro of SARS-CoV-2 and ACE2 receptor than hydroxychloroquine and could be used as a therapeutic candidate against COVID-19 [35]. No studies, either computational or in vitro, were reported for the compounds pectolinarigenin and gardenin B regarding their effects on SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Previous computational studies have revealed that taxifolin could be a potential inhibitor against the SARS-CoV-2 Mpro enzyme [33]. Moreover, tangeretin showed potential for the treatment and prevention of COVID-19 [34], while, hispidulin showed a better binding affinity to Mpro of SARS-CoV-2 and ACE2 receptor than hydroxychloroquine and could be used as a therapeutic candidate against COVID-19 [35]. No studies, either computational or in vitro, were reported for the compounds pectolinarigenin and gardenin B regarding their effects on SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Its hydrophobic core of M17 has a hydropathic index 1.9 demonstrating that this region attracts substances capable of crossing the PM. These compounds' cell invading ability further is explained by MLOGP evaluation (Table 1) (Alves et al, 2021;Moriguchi et al, 1992;Rocha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After that, the files were uploaded and submitted to the web-based tool, SwissDock (http://www.swissdock.ch/docking#) (Webb & Sali, 2019), Swiss Institute of Bioinformatic (SIB) server, for molecular docking simulation. Subsequently, the results received were processed in the UCSF Chimera® software, for analysis and comparison of the distances and interactions of curcumins with the interaction amino acid residues of N3, Azithromycin(AZT), and Baricitinib(BRT) (Alves et al, 2021;Rocha et al, 2021). From the distances obtained, the data were computed and plotted on the web-based tool, Morpheus (https://software.broadinstitute.org/morpheus/), and heatmaps were used to visualize changes in the ligand-residue interaction profiles (L-R's), being evaluated by the Pearson statistical test to detect similarity.…”
Section: Methodsmentioning
confidence: 99%
“…They have shown various modes of action including targeting viral attachment, its entry and multiplication, and suppressing inflammation [30]. Tangeretin, a citrus polymethoxyflavone compound, which is generally found in citrus peel oil is found to be greatly effective in COVID-19 treatment [31]. Similarly, other important plants like the Curcumin longa, Oroxylum indicum, Echinacea purpurea, Cinchona sp., Glycyrrhiza glabra, Ocimum sanctum, Withania somnifera and many others have reported immensely in treating COVID-19 disease.…”
Section: Potential Targets Of Medicinal Plants In Covid-19 Pathogenesismentioning
confidence: 99%
“…The anti-inflammatory activity of medicinal plants can check the cytokine storm in the affected patients and inhibit viral entry and replication [30]. Tangeretin, a citrus polymethoxyflavone compound, which is generally found in citrus peel oil is found to be effective in COVID-19 treatment [31]. Cannabis sativa, which has been used for various medical purposes, has shown anti-inflammatory activity associated with COVID-19 infection [91].…”
Section: Inflammationmentioning
confidence: 99%